Analysis of the impact of coronavirus on gross domestic product by large economic activities in Peru - Ordinola Valdez, Andrea Carmen Lidia (2021)
The objective of this study was to analyze the gross domestic  product (GDP) in relation to the major economic activities dedicated to extraction, transformation and services in our country, between the first quarter of 2007 and the second quarter of 2020, taking into account the debacle caused by COVID-19 in economic activities. The investigation was quantitative, explanatory, based on the statistical and econometric analysis of the data; assessing the assumption of no autocorrelation, the assumption of no multicollinearity and the assumption of homoscedasticity, concentrating our conclusion in the last period of our research that coincides with the period of national quarantine. The investigation concludes that the coronavirus effects have had a negative impact on most of the economic activities.